Pemberdayaan Masyarakat melalui Pengembangan Polikultur Bandeng dan Udang di Desa Karangsong, Indramayu, Jawa Barat - Aris Darmansah; . Sulistiono; Thomas Nugroho; Eddy Supriyono (Institut Pertanian Bogor, 2016)
Karangsong Village is one of the coastal villages in Indramayu which has a high fishery and marine resources potential, (both capture and aquaculture fisheries). The aquaculture activities in this village were mostly milkfish and prawn cultures. Community development through polyculture activity in this village had been done for 2 years 4 months from December 2012 to April 2015. This activity aimed to improve the community skill, especially milk fish and prawn using polyculture system. Methode used in this activity was training and empowering. The community was trained about pond culture preparation and milk fish and prawn culture methods. The community participated in first year was 4 people, and second year was 9 people. Aid distribution scheme of this program was 1 package for each fish-farmer contained prawn seed, milkfish seed, and fish-prawn feed. Through effectively empowering program, people knowledge, technology, biomass farming, and income (912 million from milkfish farming; 920 million from shrimp farming) were increased.